Precision measurement of relative γ-ray intensities from the decay of 61Cu. (April 2021) - Bleuel, D.L.; Bernstein, L.A.; Marsh, R.A.; Morrell, J.T.; Rusnak, B.; Voyles, A.S.
Abstract: A discrepancy, well outside reported uncertainties, has been observed between the accepted and measured values of the intensity ratio of the two strongest γ rays following 61 Cu β + decay. This discrepancy has significant impact since the n a t Ni(d, x) 61 Cu reaction has historically been one of only a few IAEA recommendations for use as a deuteron flux monitor and a considerable number of published cross sections measured in ratio to that beam monitor cross section may depend on the choice of either the first or second strongest γ ray in those calculations. To determine the magnitude of this error most precisely, over a hundred separate measurements of the 283 keV to 656 keV γ -ray emission ratio were collected from seven experiments and a variety of detectors and detection geometries. A weighted average of all these measurements indicates an error in the value listed in the Nuclear Data Sheets of 11% in either the primary or second-highest intensity γ ray of 61 Cu, potentially introducing an 11% error in 61 Cu production cross section measurements, cross sections using nickel activation as a deuteron beam current monitor, or in dose rates when 61 Cu is used in nuclear medicine. General agreement with the Data Sheets with ten other intensity ratios suggests the most probable error is in the secondary (656 keV) emission, which accordingly should be updated from 10.8% to 9.69%. Highlights: We observed a nuclear data error in the ratio of the two strongest 61 Cu γ rays. IAEA-recommended beam monitor cross sections may be affected. We recommend the 656 keV gamma-ray intensity in the Data Sheets be reduced by 10%.